Persepsi Followers pada Akun Instagram @gooddayid - Marcelia Kiki Farista; Muhammad Noor Hidayat (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Instagram is the second most used social media platform in Indonesia after WhatsApp social media which has a percentage of 90.9.7% of users. Meanwhile, Instagram has a percentage of 85.3% as of January 2024, namely with 139 million users. Kopi Good Day Indonesia uses Instagram as one of its digital marketing strategies. The purpose of this study was to determine the perception of followers of the Instagram account @gooddayid. This study uses a qualitative method with the subject being Generation Z in Semarang City. Based on the analysis that has been carried out by the researcher, it shows that the perception that is built on Instagram followers @gooddayid, Many factors influence perception, such as personal experiences of Instagram users with content, interest in coffee products, and the visual communication style displayed by the Kopi Good Day account. Kopi Good Day has become the first brand that comes to mind for the five informants when talking about instant coffee products that are suitable for accompanying relaxing time